Market and Technology Access Through Firm Acquisitions: Beyond One Size Fits All - Katrin Hussinger; Christoph Grimpe (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Firm acquisitions have been shown to serve as a way to gain access to international markets, technological assets, products or other valuable resources of the target firm. Given this heterogeneity of takeover motivations and the skewness of the distribution of the deal value we show whether and how the importance of different takeover motivations changes along the deal value distribution. Based on a comprehensive dataset of 652 European mergers and acquisitions in the period from 1997 to 2003, we use quantile regressions to decompose the deal value at different points of its distribution. Our results indicate that the importance of technological assets is indeed higher for smaller target firms. The findings support the view on small acquisition targets to complement the acquirer?s technology portfolio while larger acquisition targets tend to be used to gain access to international markets.
Keywords: G34; L20; O34; 330; Firm acquisitions; technological assets; market access; quantile regression; Übernahme; Fusion; Wettbewerbsstrategie; Internationale Markteintrittsstrategie; Technologietransfer; Wissenstransfer; EU-Staaten